Distorted surfaces of magnetic helium-peculiar stars: an application to a Cen. Issue 2 (10th February 2020) - Krtička, J; Mikulášek, Z; Prvák, M; Niemczura, E; Leone, F; Wade, G
ABSTRACT: Helium-peculiar magnetic chemically peculiar stars show variations of helium abundance across their surfaces. As a result of associated atmospheric scale height variations, the stellar surface becomes distorted, with helium-rich regions dented inwards. Effectively, on top of flux variations due to opacity effects, the depressed helium-rich surface regions become less bright in the optical regions and brighter in the ultraviolet. We study the observational effects of the aspherical surface on the light curves of a Cen. We simulate the light curves of this star adopting surface distributions of He, N, O, Si, and Fe derived from Doppler mapping and introducing the effect of distortion proportional to helium abundance. We show that while most of the optical and UV variations of this star result from flux redistribution due to the non-uniform surface distributions of helium and iron, the reduction of light variations due to the helium-related surface distortion leads to a better agreement between simulated optical light curves and the light curves observed with the BRITE satellites.